PENGARUH BANCASSURANCE TERHADAP PROFITABILITAS BANK DI INDONESIA - Prapanca Robiyan Pambudi; Agung Juliarto (Diponegoro Journal of Accounting, 2018)
This study aims to provide empirical evidence about the relationship between bancassurance towards profitability which is measured by Return on Assets and Return on Equity with government ownership, Capital Adequacy Ratio, and year effects as controlling variables.The objects of this study are banking companies who has bancassurance product. The sampling method of this study is purposive sampling that based on criterion which has been determined before. Hypotheses in this study are tested by descriptive statistic and data panel regression analysis method.The results of statistical test (F test) shows that bancassurance with government ownership, Capital Adequacy Ratio, and year effects as controlling variables affects profitability. The effect of independent variable bancassurance towards profitability which is proxied by Return on Assets on the t test is significant, while the effect towards profitability which is proxied by Return on Equity is not significant.